Characterizing synergistic effect of coagulant aid and membrane fouling during coagulation-ultrafiltration via in-situ Raman spectroscopy and electrochemical impedance spectroscopy. (1st April 2020) - Tang, Juan; Jia, Hui; Mu, Situ; Gao, Fei; Qin, Qingwen; Wang, Jie
Abstract: The polymer coagulant aid can effectively enhance the coagulation-ultrafiltration (C-UF) process for the purification of drinking water. However, when coagulant aid entered the filtration, it may also cause serious membrane fouling as polymer. In-situ Raman spectroscopy and electrochemical impedance spectroscopy(EIS) were applied to monitor the effects of coagulant aids on the membrane. The causes of fouling were assisted discussed through stage cleaning of the membrane. The equivalent circuit fitting was performed on the EIS data and the Raman spectral data were statistically analyzed after peak fitting. EIS and the cluster analysis of Raman spectroscopy provided an earlier feedback on membrane fouling layers compared to flux. The cause of membrane fouling was explained via variation of characteristic functional groups obtained by Raman spectroscopy. When the molecular weight of the coagulant aid was 160 times, 80 times and 16 times larger than the MWCO of the UF membrane, the equivalent circuit obtained by fitting the EIS of the UF system satisfied Rs + c(QpRp), Rs(QcRc)(QpRp) and Rs(Qt(Rc(QpRp))) respectively. Partial correlation analysis showed that the corresponding factors causing irreversible fouling of membrane were humic acid(HA), HA and coagulant aids, coagulant aids. Combined with the mean roughness (Ra) of membrane, the coagulant aid performed differently in the cleaning of contaminated membrane and also affected the cleaning of HA. Graphical abstract: Image 1 Highlights: On-line monitoring of fouling in C-UF by simultaneous Raman spectroscopy and EIS. The accumulation of foulants was explained by compound functional groups. Cluster analysis divided the membrane fouling layer into three stages. Membrane property is the key factor to role of coagulant aid in irreversible fouling.